2004
DOI: 10.1080/00016480310017090
|View full text |Cite
|
Sign up to set email alerts
|

Palatal implants: a new method for the treatment of snoring

Abstract: The new palatal implant system is safe and is associated with low morbidity. It is a fast, simple and effective treatment for snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 11 publications
6
76
3
1
Order By: Relevance
“…It is believed not to be associated with morbidity, but its impact on the snorer's social life cannot be ignored. 5,7 Therefore, this problem should be handled seriously, and the most appropriate solution should be given to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed not to be associated with morbidity, but its impact on the snorer's social life cannot be ignored. 5,7 Therefore, this problem should be handled seriously, and the most appropriate solution should be given to the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Because PI implementation is a treatment to the soft palate, like other surgical techniques, it is possible to have dysphagia, foreign body sensation, and mouth dryness, depending upon the fibrosis on the soft palate following this procedure. Nordgård et al, [3] reported a metallic taste complaint in two patients, but they had no patients with dysphagia or speech disorder. Akpinar et al [15] performed acoustic voice analysis preoperatively on 23 patients who underwent PI and on the eighth day postoperative.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is irreversible. [2][3][4] In recent years, through the popularization of minimally invasive attempts that do not require hospitalization, the popularity of soft palate surgeries for hardening the tissue have increased. Pillar implant, as well, is a new method that has been used since 2003, but the number of studies proving its long-term effects and revealing its side-effect profile are limited.…”
mentioning
confidence: 99%
“…Recent studies of isolated palate implants for snoring and OSA have demonstrated some benefit clinically, but there was no placebo control (4). Pillar procedure has been a treatment of snoring and mild-moderate sleep apnea since early 2000.…”
Section: Introductionmentioning
confidence: 99%